2023
DOI: 10.1177/20499361231162978
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent or unusual infections in children – when to worry about inborn errors of immunity

Abstract: Recurrent infections are a common presenting feature in paediatrics and, while most times considered part of normal growing up, they are also a classical hallmark of inborn errors of immunity (IEI). We aimed to outline the value of currently used signs for IEI and the influence of the changing epidemiology of infectious diseases due to implementation of new vaccines and the effect of the COVID-19 pandemic on the assessment of children with recurrent infections. Warning signs for IEI have been developed, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Throughout the COVID-19 pandemic, changes in the frequency of various infections have been observed in clinical practice [ 15 , 24 , 27 ]. In the field of otorhinolaryngology, studies have reported a reduced number of otogenic and sinogenic infections [ 10 , 17 , 19 , 23 ]. Despite the decline in infection cases, recent case reports and clinical studies have identified a worrisome trend of increased severity in sinusitis and otitis media among children, resulting in multiple intracranial complications including extensions of epidural and subdural infections, as well as cerebral venous sinus thrombosis [ 1 , 2 , 5 , 13 , 14 , 18 , 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, changes in the frequency of various infections have been observed in clinical practice [ 15 , 24 , 27 ]. In the field of otorhinolaryngology, studies have reported a reduced number of otogenic and sinogenic infections [ 10 , 17 , 19 , 23 ]. Despite the decline in infection cases, recent case reports and clinical studies have identified a worrisome trend of increased severity in sinusitis and otitis media among children, resulting in multiple intracranial complications including extensions of epidural and subdural infections, as well as cerebral venous sinus thrombosis [ 1 , 2 , 5 , 13 , 14 , 18 , 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%